2019
DOI: 10.5796/electrochemistry.17-00101
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Ni from the Acid Leaching Solution of Electroplating Sludge through Preparing Ni-Fe Alloy with the Addition of Saccharin Na First and then Thiourea

Abstract: A novel method of Ni recovery from the acid leaching solution of electroplating sludge through preparing Ni-Fe alloy with high Fe 2+ content (i.e., 0.5 g/L) is proposed in this paper, and the corresponding electrodeposition process was studied using conventional electrochemical techniques and scanning electron microscopy. The obtained results showed that adding saccharin Na at concentrations from 0 to 14 g/L to the deposition bath increased the cathodic polarization potential of Ni-Fe co-deposition, with sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…38 Organic matter can also be adsorbed on the surface of the electrode, and they can influence the interfacial charge-transfer rate of metal ion. 39 Riastuti et al claimed that SDS could be adsorbed on the cathode to prevent the deposition of nickel. 40 Ethoxylated 2-naphthalenesulfonic acid had a negative effect on the deposition of tin on gold electrodes.…”
Section: Characteristics Of Electroplating Wastewatermentioning
confidence: 99%
“…38 Organic matter can also be adsorbed on the surface of the electrode, and they can influence the interfacial charge-transfer rate of metal ion. 39 Riastuti et al claimed that SDS could be adsorbed on the cathode to prevent the deposition of nickel. 40 Ethoxylated 2-naphthalenesulfonic acid had a negative effect on the deposition of tin on gold electrodes.…”
Section: Characteristics Of Electroplating Wastewatermentioning
confidence: 99%
“…The addition of Cd 2+ weakened the electrochemical reaction of Cu 2+ on the cathode and reduced the attenuation rate of Cu 2+ in the solution, the ability The micro-morphology of cathode copper obtained by the electrodeposition of copper electrolyte without adding Cd 2+ showed that the copper crystal nuclei were one-by-one spherical nodules [34] without any cracks and pores (Figure 8a). With the addition of Cd 2+ , some clear grain refinements [36] were generated based on the spherical nodules [34]. The more Cd 2+ that was added, the finer the sediments that were generated on the compact surface and the larger the pores between each crystal (Figure 8b-f).…”
Section: Third Stage Of Cyclone Electrowinningmentioning
confidence: 99%
“…Saccharin has consistently been one of the most commonly used organic additives. [16][17][18] During the polishing process, it significantly enhances the wetting and dispersion properties of the polishing solution, contributing to a more uniform polishing process. Furthermore, this compound can form a protective film on the metal surface, reducing oxidation and other adverse reactions, effectively improving the quality of the passivation layer.…”
Section: Introductionmentioning
confidence: 99%